Vibration fatigue dynamic stress simulation under multi-load input condition: Application to metro lifeguard. (May 2019) - Li, Fansong; Wu, Pingbo; Zeng, Jing; Liu, Chaotao; Wu, Hao
Abstract: The formula for calculating the time history of structure dynamic stress under multi-load input condition was deduced based on structural dynamics theory, and fatigue life prediction of weld toe was performed by notch stress approach. In the dynamic stress time history simulation method, firstly, we calculate the frequency response function (FRF) of each external load at concerned point, which including the phase information. Then, the method was based on fast Fourier transform (FFT) to get the frequency domain with real and imaginary part of each external load rather than power spectrum density (PSD) calculation, avoiding loss of the phase information by PSD method. Finally, the dynamic stress frequency domain data could be calculated by FFT results and FRFs, based on above, the dynamic stress time history could be acquired by Inverse FFT (IFFT) of frequency domain data. Compared with the conventional stress PSD calculation method, the method in this paper can retain the phase information of the each external load, and the formula for calculating the dynamic stress under multi-load input condition was verified effective by a metro lifeguard line test data. The line test stress results show that the damage error between the numerical stress and the experimental stress is 4.1%, which is acceptable in project. At last, the method was used to guide the lifeguard structure optimization. Highlights: A practical resonance fatigue failure case of metro lifeguard was found, and the failure cause was sought out by data analysis. The failure case was used to verify the fatigue life prediction method, and notch stress approach proposed by Radaj and Miner damage theory were verified effective by resonance fatigue failure case. The formula for calculating time history of structure dynamic stress under multi-load input condition was deduced based on structural dynamics theory. The method was based on Fast Fourier Transform (FFT) to get the frequency domain with real and imaginary part of each external load rather than power spectrum density. The frequency domain data of dynamic stress could be calculated by FFT results and load-stress frequency response functions (FRF), based on above, the dynamic stress time history could be acquired by Inverse FFT (IFFT) of frequency domain data. The line test stress results show that the damage error between the numerical stress and the experimental stress is 4.1%. The dynamic stress calculation method proposed in this paper was used to optimize the lifeguard structure which has emerged failure during working, and the new structure satisfies the design requirement.